THE EFFECT OF WAGES AND WORK TENURE ON EMPLOYEE WORK PRODUCTIVITY AT PT PERMODALAN NASIONAL MADANI (PERSERO) MEKAR BEKASI BRANCH - Muliady, Denny; Wahyuningsih, Sri; Milisani, Meirna (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
This research has a quantitative approach, descriptive and associative type. In this research the author narrowed the population, namely the number of employees of PNM Mekar Bekasi Cimahi to 70 employees. The regression value (tcount) for variable X1 (Wages) is 4,281, while the ttable value for N = 70 is 1,986. So 4,281> 1,986, it can be concluded that partially the Wage variable does have a positive influence on Employee Productivity. The regression value (tcount) for variable X2 (Work Period) is 9,642, while the ttable value for N = 70 is 1,986. So 9,642> 1,986, it can be concluded that partially the Work Period variable does have a positive influence on Student Learning Outcomes. Thus, H0 is rejected and Ha is accepted, and it can be concluded that there is a positive and significant influence between variable X2 and variable Y, because the probability value is smaller than 0.05. From the results of the ANOVA test or Ftest or Fcount, we get a value of 68,894 which is greater than Ftable of 2.74 with a significance level of 0.000 because 0.000 < 0.05, so it can be said that the Wage variable (X1) and the Work Period variable (X2) together has the same effect on the Employee Productivity variable (Y).  Based on the Summary model table which produces an R value of 0.820, this shows that 8.2% of Wages and Years of Service simultaneously (together) have a positive effect on Employee Productivity and the remaining 91.8%. The result of the R2 (R Square) value is 0.673. This shows that 67.3% of Wages and Years of Service simultaneously (together) have a positive effect on Employee Productivity while the remaining 32.7% have an effect on other factors not examined in this research.